August na peryferiach pamięci. Interpretacje wybranych numizmatów dotyczących pierwszego cesarza - Anzorge-Potrzebowska, Anna (Instytut Historyczny Uniwersytetu Wrocławskiego, 2023)
This paper deals with the reading of selected posthumous images of Augustus depicted on coins, and how opting for a particular identification changes the overtones of how the emperor is remembered. The analysis is based on coins from Philippi.
Keywords: August; Filippi; mennictwo prowincjonalne